Approaching Modern Aesthetics from the Perspective of Ernst Cassirer - Herrera Ospina, José de Jesús (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2013)
This article is an introduction to modern aesthetics from an annotated reading the sixth chapter entitled “The Aesthetics fundamental problems” of the work “Philosophy of Illustration” of the German philosopher Ernst Cassirer. From a continuous path of the six major themes of modern aesthetics is to perform the tracking of basic issues in this chapter are repetitive such as beauty, art, illustration, intuition.